A real industrial building: Modeling, calibration and Pareto optimization of energy retrofit. (May 2020) - Ascione, Fabrizio; Bianco, Nicola; Iovane, Teresa; Mauro, Gerardo Maria; Napolitano, Davide Ferdinando; Ruggiano, Antonio; Viscido, Lucio
Abstract: An existing industrial building ubicated in South Italy is investigated by applying a tailored approach to optimize energy retrofit. The baseline provides high energy consumption, which needs to be tackled to promote the transition towards more sustainable buildings. Accordingly, after a detailed energy audit, the building is modeled and simulated under EnergyPlus environment using DesignBuilder® to characterize geometry and HVAC (heating, ventilating and air conditioning) systems. The model is calibrated against metered data as concerns the trends of indoor temperatures. Different retrofit measures are investigated, i.e., replacement of windows, implementation of solar screens, use of heat recovery, optimization of HVAC operation and installation of photovoltaics of different sizes. Thus, a large domain of solutions is explored by conducting an exhaustive research through the coupling between EnergyPlus and MATLAB®. The research provides the Pareto optimization of building retrofit minimizing primary energy consumption and global cost for two different scenarios as regards the access to public incentives. The utopia point criterion is used to pick a solution from the Pareto front. Such solution can yield energy and global cost savings up to 81% and 45%, respectively, ensuring the same comfort level compared to the baseline. The primary energy consumption of the whole facility can be reduced up to 40.1 kWhp /m 2 a. The outcomes can give precious guidelines to refurbish industrial and office buildings in Mediterranean areas with a view to energy-efficiency and cost-effectiveness. Graphical abstract: Image 1 Highlights: Energy model of an industrial building is developed and calibrated vs metered data. EnergyPlus is used for simulations and MATLAB® for energy retrofit optimization. Exhaustive research of sundry retrofit measures is run to achieve the Pareto front. Energy consumption and global cost are minimized for two incentives' scenarios. The utopia point criterion is used to provide a robust retrofit strategy.